Learnings from user feedback of a novel digital mental health assessment - Funnell, Erin Lucy; Spadaro, Benedetta; Benacek, Jiri; Martin-Key, Nayra A.; Metcalfe, Tim; Olmert, Tony; Barton-Owen, Giles; Bahn, Sabine (Frontiers in Psychiatry, 2022)
Digital mental health interventions (DMHI) have the potential to address barriers to face-to-face mental healthcare. In particular, digital mental health assessments offer the opportunity to increase access, reduce strain on services, and improve identification. Despite the potential of DMHIs there remains a high drop-out rate. Therefore, investigating user feedback may elucidate how to best design and deliver an engaging digital mental health assessment. The current study aimed to understand 1304 user perspectives of 1) a newly developed digital mental health assessment to determine which features users consider to be positive or negative and 2) the Composite Interview Diagnostic Interview (CIDI) employed in a previous large-scale pilot study. A thematic analysis method was employed to identify themes in feedback to three question prompts related to: 1) the questions included in the digital assessment, 2) the homepage design and reminders, and 3) the assessment results report. The largest proportion of the positive and negative feedback received regarding the questions included in the assessment (n=706), focused on the quality of the assessment (n=183, 25.92% and n=284, 40.23%, respectively). Feedback for the homepage and reminders (n=671) was overwhelmingly positive, with the largest two themes identified being positive usability (i.e., ease of use; n=500, 74.52%) and functionality (i.e., reminders; n=278, 41.43%). The most frequently identified negative theme in results report feedback (n=794) was related to the report content (n=309, 38.92%), with users stating it was lacking in-depth information. Nevertheless, the most frequent positive theme regarding the results report feedback was related to wellbeing outcomes (n=145, 18.26%), with users stating the results report, albeit brief, encouraged them to seek professional support. Interestingly, despite some negative feedback, most users reported that completing the digital mental health assessment has been worthwhile (n=1,017, 77.99%). Based on these findings, we offer recommendations to address potential barriers to user engagement with a digital mental health assessment. In summary, we recommend include undertaking extensive co-design activities during the development of digital assessment tools, flexibility in answering modalities within digital assessment, customizable additional features such as reminders, transparency of diagnostic decision making, and an actionable results report with personalized mental health resources.